Carbonyl modified epoxy resin, degradable hand lay-up resin and preparation method
By combining carbonyl-modified epoxy resin with unmodified epoxy resin in the hand paste process, a degradable hand paste resin composite material is solved, and the problem of difficult resin recovery in the existing hand paste process is achieved, the degradation of epoxy resin and the recycling of reinforced fibers are achieved, and good mechanical properties are maintained.
Patent Information
- Application Number
- CN202510017060.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
AI Technical Summary
Thermal curing resin used in the existing hand paste process is difficult to recycle, resulting in waste of resources and environmental pollution. The existing degradable epoxy resin system still has problems that are difficult to degrade when it is scrapped.
The carbonyl-modified epoxy resin is used in combination with the unmodified epoxy resin, and a degradable hand paste resin composite material is formed through a specific preparation method and process flow. The material can be degraded in an alkaline environment to separate the reinforcing fibers and realize the recycling of the fibers.
The degradability of epoxy resin is improved, the separation between epoxy resin and reinforcing fiber is optimized, and the recycling of reinforcing fiber is realized, and the mechanical properties during use are consistent with traditional hand paste resins.
Smart Images

Figure BDA0005230214880000091 
Figure BDA0005230214880000101 
Figure BDA0005230214880000102
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer compounds, and in particular to a carbonyl-modified epoxy resin, a degradable hand-lay-up resin and a preparation method thereof. Background Art
[0002] The hand lay-up process is a process method that uses manual labor to alternately lay the reinforcement material and resin on the mold, and then makes the product through curing and demoulding. At present, the resins used in the hand lay-up process are mostly thermosetting resins, which have the advantages of good mechanical properties, heat resistance, and chemical corrosion resistance. After curing into a cross-linked network, it has the characteristics of insolubility and infusibility, but it is difficult to recycle. At present, the scrapped composite materials are mostly buried and incinerated, which puts great pressure on the environmental protection, and the reinforcement materials in the composite materials are buried, resulting in a waste of resources. Therefore, it is very important to develop a degradable epoxy resin hand lay-up composite material.
[0003] Chinese invention patent CN103012747A discloses a degradable mixed polyamine epoxy resin curing agent, preparation and composite material recovery. The prepared curing agent can be made into a reinforced composite material together with an epoxy resin system, a reinforcing material and an auxiliary material. The material can also be degraded and recycled, but the degradation of the epoxy resin system cannot be achieved, and there is still a problem of difficulty in scrapping. Chinese invention patent CN103242509B discloses a degradable cyclic acetal, cyclic ketal diamine epoxy resin curing agent and its application. The curing agent can polymerize with epoxy resin to generate a degradable cross-linked polymer, and degrade in a mixed system of acid and solvent, but when acid degradation is performed, environmental pollution problems will still occur. Summary of the invention
[0004] In order to develop a degradable epoxy resin hand lay-up composite material, the first aspect of the present invention provides a carbonyl-modified epoxy resin, the structural formula of which is as follows:
[0005] Where: R is selected from One of the straight-chain alkyl and straight-chain alkenyl groups.
[0006] As a preferred embodiment, the carbon number of the straight-chain alkyl group is 1-3 or 12-14.
[0007] A second aspect of the present invention provides a method for preparing a carbonyl-modified epoxy resin, comprising the following steps:
[0008] S1: dissolving diethanolamine and diethylene ketone in a solvent to carry out diketoester-alcoholamine esterification reaction; after reacting for 2-4 hours, adding ethanol and performing reduced pressure distillation to obtain acetoacetate monoamine;
[0009] S2 carries out an amination reaction between acetoacetate monoamine and monoepoxy glycidyl ether to obtain a carbonyl-modified epoxy resin.
[0010] As a preferred embodiment, the molar ratio of diethanolamine to diethylene ketone is 1:(1-3).
[0011] As a preferred embodiment, the molar ratio of diethanolamine to diethylene ketone is 1:2.
[0012] As a preferred embodiment, the solvent is chloroform or tetrahydrofuran.
[0013] As a preferred embodiment, the amount of the solvent added is 2.5-4 times the total amount of diethanolamine and diethylene ketone.
[0014] As a preferred embodiment, the added amount of the solvent is 3 times the total amount of diethanolamine and diethylene ketone.
[0015] As a preferred embodiment, the molar ratio of the acetoacetate monoamine to the monoepoxy glycidyl ether is 1:(1-3).
[0016] As a preferred embodiment, the molar ratio of the acetoacetate monoamine to the monoepoxy glycidyl ether is 1:1.
[0017] As a preferred embodiment, the reaction temperature of the amination reaction is 20-30° C., and the reaction time of the amination reaction is 2-4 h.
[0018] As a preferred embodiment, the reaction temperature of the amination reaction is 25° C., and the reaction time of the amination reaction is 3 h.
[0019] The third aspect of the present invention provides a degradable hand-layup resin composite material, wherein the raw materials for preparation include 20-45% epoxy resin matrix and 55-80% reinforcing fiber in weight percentage, and the epoxy resin matrix includes the carbonyl-modified epoxy resin.
[0020] The inventor found in the experimental process that the combination of carbonyl-modified epoxy resin and unmodified epoxy resin can improve the degradability of epoxy resin, optimize the separation of epoxy resin and reinforcing fiber, and achieve the recycling effect of reinforcing fiber. The mechanical properties of the combined resin do not change when in use. The possible reason is that the carbonyl-modified epoxy resin and the unmodified epoxy resin have good compatibility when used, and there is no mechanical property problem caused by poor compatibility. When degraded after retirement, the carbonyl-modified epoxy resin has a certain promoting effect on the unmodified epoxy resin. In the alkaline degradation liquid, the unmodified epoxy resin undergoes a ring-opening reaction. At the degradation temperature, the epoxy resin molecular chain breaks, and the binding performance with the reinforcing fiber decreases, thereby achieving the degradation of the epoxy resin. The weight ratio of carbonyl-modified epoxy resin to unmodified epoxy resin is 7:93, which can balance good degradation performance and working mechanical strength. If the mass proportion of carbonyl-modified epoxy resin is too large, it will lead to a decrease in mechanical strength and affect the service life of the composite material.
[0021] As a preferred embodiment, the reinforcing fiber is selected from one or a combination of carbon fiber, glass fiber, mineral fiber, metal fiber, and organic synthetic fiber.
[0022] As a preferred embodiment, the epoxy resin matrix comprises 60-85% of the epoxy resin composition and 15-40% of the amine curing agent, based on the weight percentage of the epoxy resin matrix; the epoxy resin composition comprises an uncarbonyl-modified epoxy resin and a carbonyl-modified epoxy resin.
[0023] As a preferred embodiment, the non-carbonyl modified epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, multifunctional epoxy resin, novolac epoxy resin, and alicyclic epoxy resin.
[0024] As a preferred embodiment, the amine curing agent is selected from at least one of aliphatic polyamines, polyamides, polyetheramines, and imidazole curing agents.
[0025] As a preferred embodiment, the amine curing agent is an aliphatic polyamine.
[0026] As a preferred embodiment, the weight ratio of the non-carbonyl-modified epoxy resin to the carbonyl-modified epoxy resin is (88-100):(0-12), and the added amount of the carbonyl-modified epoxy resin is not zero.
[0027] A fourth aspect of the present invention provides a method for preparing a degradable hand-layup resin composite material, comprising the following steps:
[0028] S1 brushes the epoxy resin matrix on the mold, then lays the reinforcing fiber on it, and then squeezes the reinforcing fiber to make it evenly immersed in the epoxy resin matrix and eliminate bubbles;
[0029] After removing the bubbles in step S2, apply the epoxy resin matrix for the second time, and repeat step S1 to complete the hand lay-up process;
[0030] S3 is cured and formed.
[0031] As a preferred embodiment, in step S1, the epoxy resin matrix can be brushed on the preformed mold, or on the flat mold, and then the reinforcing fibers coated with the epoxy resin matrix are transferred to the surface of the object to be applied.
[0032] As a preferred embodiment, the curing molding is heating curing molding or curing molding using the heat released when the resin system is cured.
[0033] As a preferred embodiment, the curing temperature is 40-100° C. and the curing time is 4-10 h.
[0034] The degradable hand-layup resin composite material prepared by the invention can be heated and degraded with a degradation liquid in an alkaline environment to separate the reinforcing fibers, and the reinforcing fibers can be recycled.
[0035] As a preferred embodiment, the mass ratio of the degradable hand-lay-up resin composite material to the degradation liquid is 1:
[0036] (5-25); The temperature range of the heating degradation is 60-180°C, and the degradation time is 1-48h.
[0037] As a preferred embodiment, the degradation liquid is an amine compound. Preferably, the amine compound is at least one selected from aniline, benzylamine, p-methylbenzylamine, tertiary amine, alicyclic amine and heterocyclic amine.
[0038] As a preferred embodiment, the degradable hand-layup resin composite material can be applied to wind turbine blades, yachts, fishing boats, automobile interior decoration parts, automobile shells, battery boxes, switch boxes, and oil tanks.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) The degradable hand-layup resin composite material of the present invention uses a carbonyl-modified epoxy resin in combination with an unmodified epoxy resin, which can improve the degradability of the epoxy resin, optimize the separation of the epoxy resin and the reinforcing fiber, and achieve the recycling effect of the reinforcing fiber.
[0041] (2) In the degradable hand-layup resin composite material of the present invention, the weight ratio of the carbonyl-modified epoxy resin to the unmodified epoxy resin is 7:93, which can balance good degradation performance and working mechanical strength.
[0042] (3) The degradable hand-layup resin composite material of the present invention does not require changes to the existing hand-layup molding process, can directly replace the existing non-degradable epoxy resin composition, does not require changes to the production line, and has low production costs.
[0043] (4) The degradable hand-layup resin composite material of the present invention can achieve degradation and separation of the epoxy resin matrix and the reinforcing fiber under degradation conditions after reaching the scrap age. The recovered resin liquid and fiber raw materials can be reused, thus achieving green environmental protection and sustainable development.
[0044] (5) The degradable hand-layup resin composite material of the present invention has good tensile strength during use, and under double 85 aging conditions, the tensile strength does not decrease significantly, and has good aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 : are infrared spectra of epoxy resin compositions; (a) an epoxy resin composition not containing a carbonyl-modified epoxy resin, and (b) an epoxy resin composition prepared in Example 3.
[0046] Figure 2 The biodegradable hand-layup resin composite material prepared in Example 3;
[0047] Figure 3 The fibers are recycled after degradation of the degradable hand-lay-up resin composite material prepared in Example 3;
[0048] Figure 4 This is a picture of the mixed granulation of fibers recycled after degradation of the degradable hand-layup resin composite material prepared in Example 3 and PA thermoplastic masterbatch. DETAILED DESCRIPTION
[0049] Example 1
[0050] A carbonyl-modified epoxy resin, and a preparation method thereof, comprising the following steps:
[0051] S1: dissolving diethanolamine and diethylene ketone in a solvent to carry out diketoester-alcoholamine esterification reaction; after reacting for 2-4 hours, adding ethanol and performing reduced pressure distillation to obtain acetoacetate monoamine;
[0052] S2 carries out an amination reaction between acetoacetate monoamine and monoepoxy glycidyl ether to obtain a carbonyl-modified epoxy resin.
[0053] The molar ratio of diethanolamine to diethylene ketone is 1:2.
[0054] The molar ratio of the acetoacetate monoamine to the monoepoxy glycidyl ether is 1:1.
[0055] The solvent is chloroform, and the added amount of the chloroform is 3 times the total amount of diethanolamine and diethylene ketone.
[0056] The reaction temperature of the amination reaction is 25° C., and the reaction time of the amination reaction is 3 h.
[0057] A degradable hand-layup resin composite material comprises raw materials including 30% epoxy resin matrix and 70% reinforcing fiber in weight percentage.
[0058] The reinforcing fiber is Taibo-EBX800 fiber fabric.
[0059] Calculated by weight percentage of the epoxy resin matrix, the epoxy resin matrix comprises 75% of the epoxy resin composition and 25% of the amine curing agent.
[0060] The amine curing agent is polyetheramine purchased from Huntsman, USA, with the brand name D230.
[0061] The epoxy resin composition comprises an uncarbonyl-modified epoxy resin and a carbonyl-modified epoxy resin in a weight ratio of 99:1.
[0062] The non-carbonyl modified epoxy resin is bisphenol A type epoxy resin, and the model is Nan Ya 128.
[0063] A method for preparing a degradable hand-lay-up resin composite material comprises the following steps:
[0064] S1 brushes the epoxy resin matrix on the mold, then lays the reinforcing fiber on it, and then squeezes the reinforcing fiber to make it evenly immersed in the epoxy resin matrix and eliminate bubbles;
[0065] After removing the bubbles in step S2, apply the epoxy resin matrix for the second time, and repeat step S1 6 times to complete the hand lay-up process;
[0066] S3 is cured and formed.
[0067] The curing temperature is 60° C. and the curing time is 4 hours.
[0068] The prepared degradable hand-lay-up resin composite material is cut into samples for degradation, and the mass ratio of the degradable hand-lay-up resin composite material to the degradation liquid is 1:10; the temperature range of the heating degradation is 100° C., and the degradation time is 3 hours.
[0069] The degradation liquid is p-methylbenzylamine; the size of the sample block is 10 cm×10 cm.
[0070] Example 2
[0071] A degradable hand-layup resin composite material, the preparation raw materials include 30% epoxy resin matrix and 70% reinforcing fiber in weight percentage. The epoxy resin composition includes uncarbonyl modified epoxy resin and carbonyl modified epoxy resin, the weight ratio is 88:12.
[0072] The rest of the implementation is the same as Example 1.
[0073] Example 3
[0074] A degradable hand-layup resin composite material, the raw materials for preparation include 30% epoxy resin matrix and 70% reinforcing fiber in weight percentage. The epoxy resin composition includes uncarbonyl modified epoxy resin and carbonyl modified epoxy resin, the weight ratio of which is 93:7.
[0075] The rest of the implementation is the same as Example 1.
[0076] The infrared spectrum of the prepared epoxy resin composition is shown in Figure 1 (b).
[0077] The prepared biodegradable hand-lay-up resin composite material is shown in Figure 2 The fiber recovered after degradation of the prepared biodegradable hand-laid resin composite material is shown in Figure 3 The prepared biodegradable hand-layup resin composite material is a picture of the recycled fiber and PA thermoplastic masterbatch mixed granulation. Figure 4 .
[0078] Example 4
[0079] A degradable hand-layup resin composite material comprises raw materials comprising 20% epoxy resin matrix and 80% reinforcing fiber in weight percentage.
[0080] The rest of the implementation is the same as Example 3.
[0081] Example 5
[0082] A degradable hand-layup resin composite material comprises raw materials including 45% of epoxy resin matrix and 55% of reinforcing fiber in weight percentage.
[0083] The rest of the implementation is the same as Example 3.
[0084] Example 6
[0085] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:5; the heating degradation temperature range is 100°C, the degradation time is 3h, the degradation rate is 80.2%, and the degradation liquid is aniline.
[0086] Example 7
[0087] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the temperature range of the heating degradation is 100°C, the degradation time is 3h, the degradation rate is 91.4%, and the degradation liquid is benzylamine.
[0088] Example 8
[0089] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:20; the temperature range of the heating degradation is 100°C, and the degradation time is 3h. The degradation rate is 91.4%. The degradation liquid is p-methylbenzylamine.
[0090] Example 9
[0091] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:25; the temperature range of the heating degradation is 100°C, the degradation time is 3h, the degradation rate is 91.3%, and the degradation liquid is aniline.
[0092] Example 10
[0093] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 60°C, the degradation time is 3h, the degradation rate is 75.3%, and the degradation liquid is benzylamine.
[0094] Embodiment 11
[0095] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the temperature range of the heating degradation is 80°C, the degradation time is 3h, the degradation rate is 85.1%, and the degradation liquid is p-methylbenzylamine.
[0096] Example 12
[0097] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 120°C, the degradation time is 3h, the degradation rate is 93.7%, and the degradation liquid is aniline.
[0098] Embodiment 13
[0099] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the temperature range of the heating degradation is 140°C, the degradation time is 3h, the degradation rate is 94.3%, and the degradation liquid is benzylamine.
[0100] Embodiment 14
[0101] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the temperature range of the heating degradation is 160°C, and the degradation time is 3h. The degradation rate is 94.7%. The degradation liquid is p-methylbenzylamine.
[0102] Embodiment 15
[0103] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 180°C, the degradation time is 3h, the degradation rate is 94.8%, and the degradation liquid is aniline.
[0104] Example 16
[0105] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 120°C, the degradation time is 1h, the degradation rate is 70.2%, and the degradation liquid is aniline.
[0106] Embodiment 17
[0107] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the temperature range of the heating degradation is 120°C, and the degradation time is 5h. The degradation rate is 94.1%. The degradation liquid is p-methylbenzylamine.
[0108] Embodiment 18
[0109] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 120°C, the degradation time is 10h, the degradation rate is 94.5%, and the degradation liquid is aniline.
[0110] Embodiment 19
[0111] A degradable hand-layup resin composite material and a preparation method thereof, the specific implementation manner is the same as that of Example 3, except that the mass ratio of the degradable hand-layup resin composite material to the degradation liquid is 1:15; the heating degradation temperature range is 120°C, the degradation time is 20h, the degradation rate is 94.8%, and the degradation liquid is aniline.
[0112] Embodiment 20
[0113] A degradable hand-layup resin composite material and a preparation method thereof, wherein the degradation liquid after degradation in Example 17 is used, an amine curing agent is added and mixed evenly, the mixture is heated to 60° C. and cured for 4 hours, and a mechanical property test is performed.
[0114] The weight ratio of the degraded liquid to the amine curing agent is 70:20. The amine curing agent is polyetheramine purchased from Huntsman, USA, with the brand name D230.
[0115] Comparative Example 1
[0116] A biodegradable hand-layup resin composite material, the specific implementation manner is the same as that of Example 1, except that the epoxy resin composition is an uncarbonyl-modified epoxy resin.
[0117] The infrared spectrum of the prepared epoxy resin composition is shown in Figure 1 (a).
[0118] Comparative Example 2
[0119] A biodegradable hand-layup resin composite material and a preparation method thereof are provided. Conventional hand-layup resin and an amine curing agent are uniformly mixed, cured at 60° C. for 4 hours, and mechanical property tests are performed.
[0120] The conventional hand-lay-up resin is bisphenol A epoxy resin, and the model is Nan Ya 128.
[0121] The weight ratio of the conventional hand-layup resin to the amine curing agent is 75:25. The amine curing agent is polyetheramine purchased from Huntsman, USA, with a brand number of D230.
[0122] Performance Testing
[0123] 1. Glass transition temperature Tg: Refer to ISO 11357-2 standard to test the glass transition temperature.
[0124] After the degradation is completed, the recovered liquid and solid recovered material are obtained, and the weight of the solid recovered material is weighed.
[0125] 2. Actual solid recovery ratio (%) = (original FRP plate weight - solid recovery material weight) / original FRP plate weight × 100%.
[0126] 3. Degradation rate (%) = 1-((actual solid recovery ratio-theoretical composite ratio) / theoretical resin ratio) × 100%). The test results are shown in Table 1.
[0127] Table 1
[0128]
[0129] 4. Degradation rate (%): The degradable hand-lay-up resin composite materials of Examples 1-5 and Comparative Example 1 were cured at 40°C for 4 hours, 80°C for 10 hours, and 100°C for 10 hours, respectively, and the degradation rates were tested. The test results are shown in Table 2.
[0130] Table 2
[0131]
[0132] 5. Tensile strength: The degradable hand-layup resin composite materials of Example 3 and Comparative Example 1 were cured at 60°C for 4 h, 80°C for 10 h, and 100°C for 10 h, respectively, and then aged for 1000 h in a wet heat test chamber at 85°C and 85% humidity, and then the tensile strength was tested with reference to ISO 527-5 standard.
[0133] 6. Tensile modulus: The degradable hand-layup resin composite materials of Example 3 and Comparative Example 1 were cured at 60°C for 4 h, 80°C for 10 h, and 100°C for 10 h, respectively, and then aged for 1000 h in a wet heat test chamber at 85°C and 85% humidity, and then tested for tensile modulus with reference to ISO 527-5 standard.
[0134] The test results are shown in Table 3.
[0135] Table 3
[0136]
[0137]
[0138] 7. The tests of tensile strength, tensile modulus and tensile strain at break refer to ISO 527-2.
[0139] 8. The test of maximum bending stress and bending modulus shall refer to ISO 178 standard.
[0140] The test results are shown in Table 4.
[0141] Table 4
[0142]
Claims
1. A carbonyl-modified epoxy resin, characterized in that: Its structural formula is as follows: Where: R is selected from One of the straight-chain alkyl and straight-chain alkenyl groups.
2. The carbonyl-modified epoxy resin according to claim 1, characterized in that: The linear alkyl group has 1-3 or 12-14 carbon atoms.
3. A method for preparing a carbonyl-modified epoxy resin according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: dissolving diethanolamine and diethylene ketone in a solvent to carry out diketoester-alcoholamine esterification reaction; after reacting for 2-4 hours, adding ethanol and performing reduced pressure distillation to obtain acetoacetate monoamine; S2 carries out an amination reaction between acetoacetate monoamine and monoepoxy glycidyl ether to obtain a carbonyl-modified epoxy resin.
4. The method for preparing the carbonyl-modified epoxy resin according to claim 3, characterized in that: The molar ratio of diethanolamine to diethylene ketone is 1:(1-3).
5. A degradable hand-lay-up resin composite material, characterized in that: In terms of weight percentage, the raw materials include 20-45% of epoxy resin matrix and 55-80% of reinforcing fiber, and the epoxy resin matrix includes the carbonyl-modified epoxy resin according to any one of claims 1-2.
6. The degradable hand-layup resin composite material according to claim 5, characterized in that: The reinforcing fiber is selected from one or a combination of carbon fiber, glass fiber, mineral fiber, metal fiber, and organic synthetic fiber.
7. The degradable hand-layup resin composite material according to claim 5, characterized in that: Calculated by weight percentage of the epoxy resin matrix, the epoxy resin matrix comprises 60-85% of the epoxy resin composition and 15-40% of the amine curing agent; the epoxy resin composition comprises an uncarbonyl-modified epoxy resin and a carbonyl-modified epoxy resin.
8. The degradable hand-layup resin composite material according to claim 7, characterized in that: The weight ratio of the non-carbonyl-modified epoxy resin to the carbonyl-modified epoxy resin is (88-100):(0-12), and the added amount of the carbonyl-modified epoxy resin is not zero.
9. A method for preparing the degradable hand-lay-up resin composite material according to any one of claims 5 to 8, characterized in that: The following steps are involved: S1 brushes the epoxy resin matrix on the mold, then lays the reinforcing fiber on it, and then squeezes the reinforcing fiber to make it evenly immersed in the epoxy resin matrix and eliminate bubbles; After removing the bubbles in step S2, apply the epoxy resin matrix for the second time, and repeat step S1 to complete the hand lay-up process; S3 is cured and molded and can be demoulded.
10. The method for preparing the degradable hand-lay-up resin composite material according to claim 9, characterized in that: The curing temperature is 40-100° C. and the curing time is 4-10 hours.
Citation Information
Patent Citations
Degradable mixed polyamine epoxy resin curing agent, and preparation and composite material recovery thereof
CN103012747A
Degradable cyclic acetal and cyclic ketal diamine epoxy resin curing agent and application thereof
CN103242509B
Curing agent for epoxy resin and low-temperature using epoxy adhesive
CN101096412A
Preparation method of functional epoxy resin curing agent
CN106397780A
High-solid-content low-viscosity epoxy curing agent for waterborne epoxy self-levelling floor and preparation method thereof
CN108864412A